Estilo da tradução, convencionalidade e mudanças na tradução: um estudo de caso sobre os padrões de escolhas do tradutor Paulo Henriques Britto - Carolina Pereira Barcellos (2016)
This dissertation draws on Corpus-based Translation Studies (BAKER, 2000; SALDANHA, 2011; WALDER, 2013) and sets out to investigate stylistic traits of a literary translator from the perspective of conventionality and shifts in translation. It examines patterns of choices made by a translator regarding conventionality (BAKER, 2007) in Brazilian Portuguese that could be found both in his work as a translator and as an author, and the consequences of these choices for the recreation of meaning in the translated texts. Shifts in translation in the cotext of conventionality itens were also investigated in order to obtain more information about the translators linguistic preferences (PEKKANEN, 2010; BLAUTH 2015). Saldanha (2011) takes into consideration the pioneering work of Baker (2000) about the style of translators in a comparable corpus, and proposes a combined approach to the investigation of style the style of the translator as well as the style of the translated text using a combination of comparable and parallel corpora to differentiate translators choices from authors choices. Baker (2007) introduces the study of conventionality associated with translator's style, drawing on a comparable corpus. The author highlights the need to further research using a parallel corpus. Munday (2008) investigates style from a different perspective than Corpus-based Translation Studies and identifies a certain degree of standardization regarding the voice of different authors when translated by the same translator. His results allowed him to make a connection between conventionality and creativity in translated texts. Walder (2013) takes into consideration all the previous researches and sets out to investigate the choices of a translator in a comparable corpus that includes samples of a contemporary translator-authors translations and his original writing. However, the author does not use a parallel corpus to investigate the influence of the source text on the translator. Magalhães and Barcellos (2015) and Magalhães and Blauth (2015) focused on the investigation of translator's style in parallel corpora without specifically addressing the study of conventionality in translated texts or its relationship to translators creativity. This dissertation aims to fill in the gaps above mentioned through the investigation of conventionality as related to creativity and translation style in a corpus including translated texts and non-translated texts from the same translator/author. Three corpora were compiled: 1) a corpus of translated texts written in Brazilian Portuguese by Paulo Henriques Britto, 2) a corpus of non-translated texts written in Brazilian Portuguese by Britto, and 3) a corpus of short stories written in American English by the authors Philip Roth, John Updike, and Jhumpa Lahiri that, with the first corpus, the translated text by Britto, composed a parallel corpus. Two other corpora (COMPARA and ESTRA) were used as control corpora for frequency reference regarding convencionality in Brazilian Portuguese. First, statistical data were obtained using the software WordSmith Tools © 6.0 (SCOTT, 2012), and elements related to conventionality (BRITTO, 2012) in Brazilian Portuguese were analyzed at the various orders (morpheme, word, group, and clause). Second, shifts in the translated texts were investigated (CATFORD, [1965] 1978). The research methodology included compilation, preparation, alignment and tagging the texts for later analysis with WordSmith Tools © 6.0. The results indicated that Britto made a set of choices to some extent distinct for each translated text, under the influence of the style of source texts. In general, the linguistic choices made by Britto regarding the use of conventional expressions increased the degree of colloquialism in the translated texts when compared to their respective source texts. In addition, the set of choices identified in Brittos non-translated texts presented some similarities with the set of choices identified in his translated texts, in particular with the ones in Philip Roths work. The most frequent shift in translation was addition (an amplification subcategory). These instances of addition were not directly related to explicitation. They were, on the other hand, related to a preference from the translator to use conventional expressions in translated texts, even when there was no clear motivation for this in the source texts. Britto also made use of sanitization, erasing some cultural references from the source texts. Nevertheless, the translators creativity consistently outweighted the use of sanitization, corroborating the results obtained by Munday (2008) and refuting, to some extent, the ones obtained by Baker (1999, 2000).